2011
DOI: 10.1159/000331882
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 and TNF-α Polymorphisms Are Associated with Risk of Multiple Superficial Tumors or Carcinoma in situ Development

Abstract: Introduction: This study evaluates the influence of clinicopathological characteristics, bacillus Calmette-Guérin (BCG) therapeutic schedule [maintenance (mBCG) or induction (iBCG)], and TNF-α and IL-4 polymorphisms on the outcome of non-muscle-invasive bladder cancer patients treated with BCG. Material and Methods: DNA was extracted from 125 bladder cancer patients treated with BCG; TNF-308G/A and IL4-590C/T polymorphisms were genotyped. Results: The TNF-308A allele carriers had an increased risk of developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 104 publications
3
3
0
Order By: Relevance
“…We also observed that male patients presented an increased risk of recurrence after treatment. Our present findings reinforce previous associations of these clinical variables with BCG immunotherapy response and highlight the need to include them in predictive models for this therapy.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We also observed that male patients presented an increased risk of recurrence after treatment. Our present findings reinforce previous associations of these clinical variables with BCG immunotherapy response and highlight the need to include them in predictive models for this therapy.…”
Section: Discussionsupporting
confidence: 89%
“…We also observed that male patients presented an increased risk of recurrence after treatment. Our present findings reinforce previous associations of these clinical variables with BCG immunotherapy response [18,[22][23][24][25] and highlight the need to include them in predictive models for this therapy. Genetic polymorphisms in molecules involved in the BCG mechanism of action have also been recognised as good candidates to predict treatment outcome.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For this review, 373 full-text articles were evaluated in depth, resulting in a final set of 112 articles for further summary (Figure 1). In total, 316 associations were extracted across all investigated outcomes as follows: age (N = 12 11-22 ), stage (N = 79 11,13,18,20,23-66 ), tumor size (N = 2 67,68 ), grade (N = 49 11,18,27,29,32,33,35…”
Section: Resultsmentioning
confidence: 99%
“…Broadly, we have differentiated between stages corresponding to NMIBC and MIBC cases. For studies reporting on NMIBC, the following endpoints were used: tumors of Tis, 61,65 T1, 37 Ta + T1, 13,18,36,39,54,58,[62][63][64]66 and Ta + T1 + Tis 32,59,60 (Supplementary Table 4). As for MIBC, most studies have defined the primary outcome as T2+ staged tum ors.…”
Section: Resultsmentioning
confidence: 99%